A linear theory of gravitation - Bollini, Carlos Guido (1970)
Deser and Laurent found recently a linear, nonlocal theory of gravitation which satisfies the experimental tests of general relativity. Their theory leads to a tensor field for the static point particle, identical to the linearized Sehwarzschild solution, namely: [fórmula]. In this paper we present an alternative theory which we think simpler and more transparent than D. L.'s theory, and, further, it leads to the same results. Both theories coincide when the energy - momentum tensor is conserved.